The prevalence of post-traumatic stress disorder among landslide victims - Lateh, Habibah; Ahmad, Jamilah; Mohamad, Nur Afiqah (MedCrave Group, 2018)
Malaysia has been prone to both natural and man-made disasters such as droughts, flood, landslides, haze and others. These disasters affect livelihoods, destroy infrastructure, cause food shortages and health problems. People exposed to natural disasters have a greater risk of experiencing mental health problems, including posttraumatic stress disorder (PTSD). This must have been a terrible experience with psychological consequences. The purpose of this study to investigate the prevalence of Post-Traumatic Stress Disorder (PTSD) among public that involved or have been a victim of landslides and to study the symptoms of trauma recovery by landslide for the benefit of well being.We assessed PTSD by using The Post-traumatic stress disorder checklist and Post Traumatic Growth Inventory for 500 respondent from five areas that hit by landslides. The post–traumatic stress disorder checklist, it is to test emotional trauma such as depression, psychological stress, fear, anxiety and others. The Post-traumatic Grow Inventory that test positive changes and development of the symptoms of trauma. The scale appears to have utility in determining how succesful individuals, coping with the aftermath of trauma, are in reconstructing or strengthening their perceptions of self, others and the meaning of events. We are using mix methods for this research uses purposive and snow ball sampling. The result show, some of public who experience hit by landslide had been a trauma. The location of study that most highest trauma victims is Bukit Antarabangsa 16.4% and Paya Terubong 13.25. But most of them are back to normal after trauma were 55.2%. Although traumatic or distressing events can cause long-lasting psychological symptoms but, they may report an increased interest in spritual matter, increased maturity, improved social relations or a new and healthier lifestyle after a traumatic event.